From Boekhandel Van Haren Noman To Nv Boekhandel En Drukkerij G. Kolff & Co Years 1848-1921 - Nadiah Ismi Fadilah; Salindri, Dewi; Primaditya, Krisnanda Theo (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2026)
This study examines the development of Boekhandel Van Haren Noman in Buiten Nieuwpoortstraat, Batavia, which underwent institutional transformation into a Vennotschap onder Firma and later a Naamlooze Vennootschap between 1848 and 1921, using a business sociology perspective. The study aims to explain the relationship between the growing demand for printing services and the establishment of the bookstore, as well as to analyze the changes in business organization as a strategy for capital accumulation and corporate expansion. The research employs the historical method, which includes heuristics, verification, interpretation, and historiography. The findings indicate that the increasing public demand for information and reading materials encouraged Willem Van Haren Noman to establish Boekhandel Van Haren Noman in 1848. Initially, the bookstore relied on book supplies imported form the Netherlands. However, rising transportation costs and growing for books and newspapers led the company to produce its own publications. In 1853, the business was reorganized as Van Haren Noman & Kolff. A partnership established to strengthen capital resources and distribute business responsibilities. As economic conditions and printing technology advanced, the partnership structure became less capable of supporting the company’s expansion. Partnerships faced limitations in raising capital and did not separate corporate assets from the personal wealth of partners. In contrast, the limited liability company structure enabled capital acquisition through share ownership, provided a clearer organizational framework, and separated corporate liabilities from shareholder’s personal assets. Consequently, in 1921 G. Kolff & Co was transformed into a Naamlooze Vennootschap (NV) to strengthen its institutional foundation, increase capital capacity, and support the continued growth of its printing business.